KARAKTERISTIK AFEKTIF: KARAKTERISTIK AFEKTIF - Sartika Akarama; Rahmat Olii; Frezy Paputungan (Jurnal Ilmu Pendidikan dan Budaya, 2023)
The five affective traits of (1) interests, (2) attitudes, (3) self-concept, and (4) values are crucial for learning. Affective assessment seeks to: 1) ascertain students' interest in accounting subjects, which can then be used to boost interest if it turns out that it is low; 2) ascertain students' attitudes toward accounting subjects, as these attitudes can be used to determine the best learning strategies for students. 3) To be aware of one's own strengths and shortcomings, which can be utilized to establish the course that students should take to select their career and 4) To disclose personal values, the material is presented as positive and negative values, with the positive values being emphasized and the negative values being subdued.